IMPLEMENTASI LEAST SIGNIFICANT BIT (LSB) DAN ALGORITMA VIGENERE CIPHER PADA AUDIO STEGANOGRAFI - Minarni Minarni; Rasyid Redha (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2020)
This study discusses the implementation of the Least Significant Bit (LSB) method and the Vigenere Cipher algorithm to maintain the confidentiality of information or data from unauthorized parties by hiding messages on media audio. LSB is used to insert messages by replacing the lowest bit in a byte of the carrier media. Vigenere Cipher cryptographic algorithm to increase message security by encoding the alphabetic text using a Caesar cipher based on the letters in the password. Testing based on steganographic criteria, namely changes in file size, fidelity, and robustness. Based on tests carried out on several mp3 audio files that have been inserted with messages with variations of 50 to 1000 characters, the results obtained that the file size does not change after the message is inserted and can be extracted again. The number of characters in a message affects the parsing time of the message. In terms of fidelity, character insertion does not change the bit rate of audio stega. Meanwhile, in terms of robustness, stega audio is not resistant to manipulation. These results indicate that the LSB method and the Vigenere Cipher algorithm on audio media can insert messages and decipher messages that have been encrypted properly without damaging the audio components.